Structural panel Bayesian VAR model to deal with model misspecification and unobserved heterogeneity problems - Antonio Pacifico (Econometrics, 2019)
This paper provides an overview of a time-varying Structural Panel Bayesian Vector Autoregression model that deals with model misspecification and unobserved heterogeneity problems in applied macroeconomic analyses when studying time-varying relationships and dynamic interdependencies among countries and variables. I discuss what its distinctive features are, what it is used for, and how it can be analytically derived. I also describe how it is estimated and how structural spillovers and shock identification are performed. The model is empirically applied to a set of developed European economies to illustrate the functioning and the ability of the model. The paper also discusses more recent studies that have used multivariate dynamic macro-panels to evaluate idiosyncratic business cycles, policy-making, and spillover effects among different sectors and countries.
Keywords: 13/A2; 13/A4; 13/A5; 13/D1; 13/D2; 330; panel VAR; Bayesian inference; structural spillovers; hierarchical priors; MCMC implementations